2018
DOI: 10.1177/2040206618811416
|View full text |Cite
|
Sign up to set email alerts
|

Activity of enisamium, an isonicotinic acid derivative, against influenza viruses in differentiated normal human bronchial epithelial cells

Abstract: Aims: New therapeutics for the control of influenza virus infections are needed to alleviate the burden caused by seasonal epidemics and occasional pandemics, and to overcome the potential risk of drug-resistance emergence. Enisamium iodide (Amizon V R , Farmak) is currently approved for clinical use for the treatment of influenza in 11 countries which includes Ukraine, Russia, Belarus, Kazakhstan, and Uzbekistan. However, experimental evidence of the antiviral activity of enisamium has not been reported. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 18 publications
8
20
0
9
Order By: Relevance
“…Previous experiments showed that enisamium iodide can inhibit influenza virus replication in tissue culture(18). To test if enisamium can inhibit IAV RNA synthesis in a minigenome context, HEK 293T cells were transfected with plasmids expressing FluPol subunits from influenza A/WSN/33 (H1N1) virus (WSN) (pcDNA3-PB1, pcDNA3-PB2, pcDNA3-PA), the viral NP (pcDNA3-NP) and a vRNA template based on segment 5 (NP-encoding genome segment).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experiments showed that enisamium iodide can inhibit influenza virus replication in tissue culture(18). To test if enisamium can inhibit IAV RNA synthesis in a minigenome context, HEK 293T cells were transfected with plasmids expressing FluPol subunits from influenza A/WSN/33 (H1N1) virus (WSN) (pcDNA3-PB1, pcDNA3-PB2, pcDNA3-PA), the viral NP (pcDNA3-NP) and a vRNA template based on segment 5 (NP-encoding genome segment).…”
Section: Resultsmentioning
confidence: 99%
“…Our in vitro assays indicate that enisamium and VM17-04 inhibit FluPol activity with relatively high IC 50 values, 46.3 mM and 0.84 mM respectively. However, enisamium strongly inhibits influenza virus growth in cell culture, with EC 90 values ranging from 157-439 µM(18). This apparent discrepancy may be due to enisamium exerting additional antiviral effects through other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…У дослідженнях in vivo на тхорах, проведеними у лабораторії «Retroscreen» (наразі -«hVivo»), Лондон, Великобританія, яким інокульовали вірус грипу через верхні дихальні шляхи, також продемонстровано противірусний ефект енісаміуму йодиду, що, зокрема, проявився у статистично достовірному зниженні вірусних титрів у носових змивах (Boltz D. et al, 2014;Boltz D. et al, 2017;Cocking D. et al, 2018).…”
Section: лікарю-практикуunclassified
“…Вступ. Енісаміум йодид (N-метил-4-бензилкарбамідопіридинію йодид), структурна формула якого наведена на рисунку 1, є антивірусним хіміотерапевтичним засобом, що застосовується для лікування грипу та ГРВІ [1,2]. Відповідно до європейських та українських підходів нормування, відхилення кількісного вмісту активного фармацевтичного інгредієнту (АФІ) має складати ±5 % від заявленої кількості [3,4].…”
unclassified